Numerical and experimental study on the parametric roll resonance for a fishing vessel with and without forward speed. (August 2020) - Ghamari, Isar; Greco, Marilena; Faltinsen, Odd M.; Lugni, Claudio
Abstract: The parametric resonance in roll motion (known shortly as parametric roll) was studied for a fishing vessel in regular waves. This is an instability and resonance phenomenon that can lead the roll to reach very high oscillation amplitudes at its natural frequency, depending on the damping level involved. In the worst cases it is responsible for vessel capsize. Here the problem was investigated numerically and experimentally, performing dedicated physical tests on a typical Norwegian fishing vessel with blunt hull and small length-to-beam ratio. Experimentally, a dedicated study was carried out on the SFH112 fishing vessel in scale 1:10 in regular head-sea waves with different wave frequencies and steepnesses. The tests were performed without and with forward speed, with corresponding Froude number Fn = 0.09 and 0.18. Numerically, a blended method was developed based on a 6-DOF 3D hybrid method where the radiation and diffraction potentials were computed for zero forward speed by WAMIT and used in the STF strip theory to obtain speed dependent loads. The convolution integrals were used to account for the effect of radiation free-surface memory effect. Nonlinearities in the Froude-Krylov and restoring loads were accounted for by integrating the corresponding pressure terms on the instantaneous wetted-hull surface defined by the incident waves and body motions. Use of the weak-scatterer hypothesis in radiation and diffraction loads has also been considered. The method was applied to reproduce and complement the experiments on the SFH112 fishing vessel. The numerical simulations showed good agreement with the experimental results. For the cases near the instability border of a 1-DOF Mathieu-type instability diagram, the physical and numerical predictions were different in terms of parametric roll occurrence. The instability borders for the experimental cases are also different from the instability borders of 1-DOF Mathieu-type instability diagram. The instability region for the experiments and 6DOF simulations cover a wider range of frequency ratio and the threshold value of metacentric height variation amplitude to have parametric roll seems to be lower than predicted by the 1-DOF Mathieu instability diagram. The results also show that the instability region for the cases with forward speed shifts to the lower frequency ratios(natural roll frequency to encounter frequency ratio) compared to the cases without forward speed. The effect of the weak-scatterer hypothesis on the results is also assessed and shown to be important for parametric roll. The results show that the simulations without this hypothesis tend to underestimate the occurrence and severity of parametric roll especially in longer and steeper waves.